The Influence of the Use of Information Technology on Internationalization Export Performance in Indonesian Micro, Small, and Medium Enterprises - Rahmawati, Santi (Applied Quantitative Analysis, 2021)
Although micro, small, and medium enterprises (MSMEs) hold an important role in Indonesian economic growth, especially MSMEs that have already done internationalization through export and the use of information technology (IT) for leveraging, there is limited data that can explain their factors and relationships that can influence export performance in order to achieve more. This study aims to analyse the roles of information technology (IT) and internationalization in explaining export performance in micro, small, and medium enterprises (MSMEs). International entrepreneurial orientation, organisational learning orientation, and product/service quality are posited as the basis of internationalization analysis. Respondents are 104 MSMEs involved in the foreign market. This study uses a quantitative method, partial least squares (PLS), to test the hypothesis. The results indicate that export performance is positively significant influenced by international entrepreneurial orientation, and product/service quality. While the use of IT does not directly influence export performance, it does positively influence organisational learning orientation. The study also shows that organisational learning orientation does not positively influence the export performance. Studies on the internationalization of micro, small, and medium businesses in developing countries are still quite limited, so the study contributes to the existing literature on internationalization and international entrepreneurship research.